Social Challenges Facing the Muslim Minority in Thailand and Ways to Deal with Them in the Light of Islamic Education - AI-yabroudi , Insherah Ahmed Tafiqi; THanijsara , Fatin Sathihjal Prasit (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This research aims to uncover the social challenges facing the Muslim minority in Thailand and clarify methods of addressing them in the context of Islamic education. Methods: The descriptive analytical method was adopted to describe the nature of social challenges and propose solutions after analyzing data collected from appropriate sources. Results: The study found that Thai law contains supportive texts and procedures for the Muslim minority but they are insufficient given the scale of the challenges. Among the most significant social challenges facing Muslims in Thailand are mixed marriages and sexual deviance. Important approaches to dealing with these challenges include the focus of Islamic educational institutions (families, schools, mosques) on instilling correct faith in the minds of children, as it is closely linked to the Muslim identity and ethics, and nurturing children in virtue and strength at different stages of their development according to clear goal-oriented methodologies. Conclusion: The research underscores the necessity of employing Islamic educational guidelines to confront social challenges and emphasizes the need for international scientific efforts to understand the challenges facing Muslim minorities and conduct applied studies on appropriate strategies for each minority in the context of Islamic education.